(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article investigates the notion of attaining spiritual and emotional freedom through art and love as reflected in the “O`tkan kunlar” (Bygone days) by Abdulla Qodiriy and Somerset Maugham`s “The Moon and Sixpence”. Literary – comparative, sociological, and philosophical – analytical tactics were utilized in the analysis. The study reveals that art and love represent as powerful forces conducting humans toward freedom and focus on both the diverse and similar aspects in the literary approaches of the two writers. This research can bolster contemporary literary studies and philosophical discourse.